Kapabilitas Dynamic Governance Koordinator Pendidikan Kecamatan Dalam Penyelenggaraan Urusan Pendidikan di Kabupaten Rokan Hulu - Al hanif, Al hanif; Zulkarnaini, Zulkarnaini; Andri, Seno (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The purpose of this study was to determine the Dynamic Governance capability of the sub-district education coordinator in the implementation of education affairs at Rokan Hulu District. The type of research used is qualitative by collecting data using observation, interviews and documentation and then the data obtained is analyzed descriptively qualitatively. The results of the study show that in implementing education affairs, the sub-district coordinator has quite optimal capability in dealing with Dynamic Governance where from a thinking ahead perspective, the sub-district coordinator must be able to plan curriculum development, identify resource needs, anticipate challenges faced by the assisted education units in the future, promoting innovation amidst the times, as well as building partnerships with relevant stakeholders. The thinking again attitude carried out by the sub-district coordinator is to carry out continuous evaluations, respond to UPTD changes, and make corrections to recommendations for comprehensive solutions to existing problems. In terms of thinking across, education coordinators still have to provide policy implications through training, overcoming complex challenges that occur in each of the assisted education units. Factors inhibiting the Dynamic Governance capability of the District Education Coordinator in the implementation of education affairs in Rokan Hulu Regency consist of limited authority to make policies and also limited human resources that cause multiple positions and increase the workload.